199k views
4 votes
How to solve 6x + y= -5, -6x + 12y=96 using elimination and does it have no solution or many solutions?

User Lazette
by
5.0k points

1 Answer

6 votes

Answer:

x = -2

Explanation:

Arrange 6x + y= -5, -6x + 12y=96 vertically:

6x + y= -5

-6x + 12y=96 Now combine like terms:

--------------------

13y = 91

Solving for y by dividing both sides by 13: y = 7

Find x by substituting 7 for y in the second equation: -6x + 12(7) = 96

Then -6x = -84 + 96, or:

-6x = 12, and so x = -2

User Dima Deplov
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.